Firing up the Tumor Microenvironment with Nanoparticle-Based Therapies - Yunfeng Pan; Xueru Song; Yue Wang; Jia Wei (MDPI AG, 2021)
Therapies mobilizing host immunity against cancer cells have profoundly improved prognosis of cancer patients. However, efficacy of immunotherapies depends on local immune conditions. The "cold" tumor, which is characterized by lacking inflamed T cells, is insensitive to immunotherapy. Current strategies of improving the "cold" tumor microenvironment are far from satisfying. Nanoparticle-based therapies provide novel inspiration in firing up the tumor microenvironment. In this review, we presented progress and limitations of conventional immunotherapies. Then, we enumerate advantages of nanoparticle-based therapies in remodeling the "cold" tumor microenvironment. Finally, we discuss the prospect of nanoparticle-based therapies in clinical application.